ANALISIS PENGARUH KEDALAMAN MAKAN DAN KECEPATAN POTONG TERHADAP GAYA PEMOTONGAN PROSES PEMBUBUTAN ALUMINIUM 6061 - Mochamad Fauzan Wirasaputra (2023)
Metalworking in the manufacturing sector frequently uses a process called turning. The fundamental idea behind turning is to use the lathe as a tool to rotate the workpiece. This research aimed to determine how feed depth and cutting speed influenced the cutting force during the machining of 6061 aluminum. Cutting force variations are a sign of changes in the feed rate, cutting depth, and machine tool condition during the machining process.. The test, which involved spinning and measuring the electric current, was done 16 times. In each experiment, the cutting force and power may be calculated from the electric current. The result is an average cutting force of 10650 N at a cutting speed of 50 rpm, 2622 N at a cutting speed of 210 rpm, 563 N at a cutting speed of 1120 rpm, and 433 N at a cutting speed of 1600 rpm. These results indicate that the value of cutting force will decrease as cutting speed increases; however, the difference in cutting force for cutting depth is not as significant.